Do able bank managers exhibit specific attributes? An empirical analysis of their investment efficiency - Isabel-María García-Sánchez; Emma García-Meca (Administrative Sciences, 2020)
We analyze the association between managerial ability in banks and three different typologies of investments that demand significant resources: capital, research and development (R&D), and acquisition expenditures. We also analyze whether managerial ability is related to increased (reduced) investment in banks prone to underinvestment (overinvestment). The sample for analysis is composed of 877 observations of banks in nine countries over the period 2004-2010. We find evidence that more able bank managers select and implement investment projects more efficiently and confirm the upper echelon theory and resource-based view, which suggests that managers' characteristics affect financial decisions. The findings are robust to alternative measures of investment efficiency. The evidence confirms that, after controlling for bank and country-specific institutional factors, managers' abilities influence investment efficiency in banks in a significant way. This paper is a response to the calls for a further exploration of the roles that individual managers play in financial decisions and is the first empirical study to investigate this association in the international financial industry.
Keywords: 350; banks; investment efficiency; managerial ability